2010
DOI: 10.1016/j.ophtha.2009.07.017
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Retinal Vein Occlusion: Pooled Data from Population Studies from the United States, Europe, Asia, and Australia

Abstract: Objective-To summarize the prevalence of retinal vein occlusion (RVO) from studies in the United States, Europe, Asia, and Australia. Design-Pooled analysis using individual population-based data.Participants-Individual participant data from population-based studies around the world that had ascertained RVO from fundus photographs.Methods-Each study provided data on branch RVO and central RVO by age, sex, and ethnicity. Prevalence rates were directly age and sex standardized to the 2008 world population aged 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
651
6
42

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 949 publications
(712 citation statements)
references
References 35 publications
13
651
6
42
Order By: Relevance
“…Previously reported prevalence of CRVO overall ranges from 0.1% 4 to 0.8%. 5 In the current study, the prevalence of 0.5% is consistent with prior reports. Although patients with CRVO have a higher prevalence of DM than the general population, 16,[21][22][23][24] in the current study the prevalence of CRVO in DM patients was 0.5%, and was not statistically different than the prevalence of 0.4% observed in the nondiabetic patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previously reported prevalence of CRVO overall ranges from 0.1% 4 to 0.8%. 5 In the current study, the prevalence of 0.5% is consistent with prior reports. Although patients with CRVO have a higher prevalence of DM than the general population, 16,[21][22][23][24] in the current study the prevalence of CRVO in DM patients was 0.5%, and was not statistically different than the prevalence of 0.4% observed in the nondiabetic patients.…”
Section: Discussionsupporting
confidence: 92%
“…[1][2][3] Population-based studies estimate that the prevalence ranges from 0.1% 4 to 0.8% 5 and that the 15-year cumulative incidence is 0.5%. 6 CRVO is observed in all age groups, with increasing incidence with advancing age.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, an estimated 16.4 million adults are affected by RVO (2.5 million by CRVO and 13.9 million by BRVO). 4 The age and sex standardized prevalence is 5.20 (per 1000) for any RVO, 4.42 for BRVO, and 0.80 for CRVO in the population aged Z30 years. 4 The prevalence of RVO in individual studies ranged from 0.3 11 to 2.1% 7 in populations older than 40 years, with the prevalence of RVO highest in Japan and Australia and lowest in Europe and Singapore ( Table 1).…”
Section: Prevalencementioning
confidence: 96%
“…In addition to one pooled analysis of existing data, 4 Eye subtypes were identified (three from the United States, and one each from Australia, China, Japan, and Singapore). [5][6][7][8][9][10][11] Although prevalence data from European countries are not available in published reports, the investigators in the EUREYE and Rotterdam Eye study were contacted by Rogers et al 4 and the data from these two studies were included in the pooled analysis and separately reported by Rogers et al 4 Overall, the prevalence of RVO appears to be fairly constant across all countries (Table 1).…”
Section: Prevalencementioning
confidence: 99%
“…Macular edema (ME) is a common complication as a major cause of visual loss in BRVO patients. 1,2 Although the exact mechanism of ME in BRVO is not fully understood, ME is thought to be caused by the flux of fluid from the blood vessels to the tissue, because of breakdown of the blood-retinal barrier as a result of damage to the tight junctions of capillary endothelial cells, enhanced expression of inflammatory cytokines such as prostaglandins and interleukin 6, and increased secretion into the vitreous of vasopermeability factors such as vascular endothelial growth factor (VEGF) produced in the retina. [3][4][5][6][7] Several recent studies have reported that VEGF has an important role in the pathophysiology of ME by inducing blood-retinal barrier breakdown and increasing vascular permeability.…”
Section: Introductionmentioning
confidence: 99%